A Study on Patient Compliance of Tuberculosis Enrolled Under Revised National Tuberculosis Control Programme - Salil Sakalle; Bhagwan Waskel; Sanjay Dixit; Dhruvendra Pandey; Suraj Sirohi; Satish Saroshe (Medsci Publications, 2014)
Background: Tuberculosis (TB) is a global health concern, India ranks first among the world's high-burden tuberculosis (TB) countries. Noncompliance to self administered multi drug tuberculosis treatment regimens is common and is the most important cause of failure of initial therapy and relapse. Objective: To assess various aspects of patient compliance to DOTS for the treatment of tuberculosis, to assess the role of socio-demographic factors, life style related factors, side effects of anti tubercular drugs in patient compliance. Material & Method: A cross sectional Study with informed written consent was conducted in 50 Sputum positive tuberculosis patients enrolled under RNTCP in Manoramaraje TB hospital (Attached to medical college & hospital) and Prakash chandsethi Hospital (UHTC) Indore. Patients were selected using convenient sampling method. All sputum positive Failure, relapse and defaulters were included in study. A predesigned, semi structured questionnaire was used as tool to interview the patients. The data was analyzed using Microsoft office excel sheet. Results: In total 50 patients, 42% females and 58% males were included in our study. 22% and 12% of patients had history of Infection at family and workplace respectively. 44 % of total patients did not complete the category I treatment. 28% of the patients were not compliant to current treatment of Category II. Most common reason behind non compliance was obtaining relief from symptom of tuberculosis. Conclusion: The disease mainly affects the low socioeconomic strata where maintenance of high level of compliance is difficult. The main reasons of low patient compliance are lack of awareness about the disease, more concern about earning the wages, low motivation during drug therapy and early appearance of side effects.